Cardiac biomarkers in pediatric cardiomyopathy: Study design and recruitment results from the Pediatric Cardiomyopathy Registry. (June 2019) - Everitt, Melanie D.; Wilkinson, James D.; Shi, Ling; Towbin, Jeffrey A.; Colan, Steven D.; Kantor, Paul F.; Canter, Charles E.; Webber, Steven A.; Hsu, Daphne T.; Pahl, Elfriede; Addonizio, Linda J.; Dodd, Debra A.; et al.
Abstract: Background: Cardiomyopathies are a rare cause of pediatric heart disease, but they are one of the leading causes of heart failure admissions, sudden death, and need for heart transplant in childhood. Reports from the Pediatric Cardiomyopathy Registry (PCMR) have shown that almost 40% of children presenting with symptomatic cardiomyopathy either die or undergo heart transplant within 2 years of presentation. Little is known regarding circulating biomarkers as predictors of outcome in pediatric cardiomyopathy. Study design: The Cardiac Biomarkers in Pediatric Cardiomyopathy (PCM Biomarkers) study is a multi-center prospective study conducted by the PCMR investigators to identify serum biomarkers for predicting outcome in children with dilated cardiomyopathy (DCM) and hypertrophic cardiomyopathy (HCM). Patients < 21 years of age with either DCM or HCM were eligible. Those with DCM were enrolled into cohorts based on time from cardiomyopathy diagnosis: categorized as new onset or chronic. Clinical endpoints included sudden death and progressive heart failure. Results: There were 288 children diagnosed at a mean age of 7.2 ± 6.3 years who enrolled in the PCM Biomarkers Study at a median time from diagnosis to enrollment of 1.9 years. There were 80 children enrolled in the new onset DCM cohort, defined as diagnosis at or 12 months prior to enrollment. The median age at diagnosis for the new onset DCM was 1.7 years and median time from diagnosis to enrollment was 0.1 years. There were 141 children enrolled with either chronic DCM or chronic HCM, defined as children ≥2 years from diagnosis to enrollment. Among children with chronic cardiomyopathy, median age at diagnosis was 3.4 years and median time from diagnosis to enrollment was 4.8 years. Conclusion: The PCM Biomarkers study is evaluating the predictive value of serum biomarkers to aid in the prognosis and management of children with DCM and HCM. The results will provide valuable information where data are lacking in children. Highlights: Pediatric cardiomyopathy is a rare but clinically important disease. There are no studies in children that reliably correlate circulating biomarkers with outcome in children with DCM or HCM. Studies of new pediatric cardiomyopathy require multi-center collaboration to yield significant results. Young age at diagnosis highlights the need to study age-related differences in pediatric versus adult cardiomyopathy.